A cross-sectional study on resilience, anxiety, depression, and psychoactive substance use among heterosexual and sexual minority adolescents in Nigeria - Olanrewaju Ibikunle Ibigbami; Olakunle Ayokunmi Oginni; Cory Bradley; Joanne Lusher; Nadia Adjoa Sam-Agudu; Morenike Oluwatoyin Folayan (BMC, 2023)
Abstract Background Mental health-related problems predispose alcohol and other psychoactive substances use as coping strategies. We assessed associations between resilience and anxiety symptoms, depressive symptoms, problematic alcohol, and multiple psychoactive substance use among sexual minority and heterosexual adolescents in Nigeria. Methods This was a secondary analysis of a subset of data generated through an online cross-sectional study conducted between 16th and 31st of October 2020. Data extracted for adolescents in Nigeria age 13-19 years were: dependent variables (alcohol use using the CAGE test, multiple psychoactive substance use, depressive symptoms using the Patient Health Questionnaire-9, and anxiety symptoms using the Generalized Anxiety Disorder-7 measure); independent variables (resilience using the Connor-Davidson resilience scale and sexual identity), and confounding factors (age and sex). Associations between dependent and independent variables were determined using multivariable logistic regression analyses after controlling for confounders. Results Of the 1419 adolescent participants, 593 (42%) were sexual minority individuals, 533 (37.6%) had high depressive symptoms, 381 (26.8%) had high anxiety symptoms, 177 (12.5%) had problematic alcohol use and 389 (27.4%) used multiple psychoactive substances. Resilience was significantly associated with lower odds of anxiety (AOR:0.96, 95% CI: 0.94-0.97, p < 0.001) and depressive (AOR:0.94, 95% CI: 0.92-0.96, p < 0.001) symptoms, problematic alcohol use (AOR:0.97, 95% CI: 0.95-0.99, p = 0.002), and multiple psychoactive substance use (AOR:0.95, 95% CI: 0.93-0.96, p < 0.001). Sexual minority adolescents had significantly higher odds of anxiety (AOR:4.14, 95% CI: 3.16-5.40, p < 0.001) and depressive symptoms (AOR:4.79; 95% CI: 3.73-6.15, p < 0.001), problematic alcohol use (AOR:2.48, 95% CI: 1.76-3.49, p < 0.001), and multiple psychoactive substance use (AOR:5.69, 95% CI: 4.34-7.47, p < 0.001). Conclusion Sexual minority adolescents and adolescents with low resilience have a higher need for interventions to reduce the risk of anxiety, depression, and the use of alcohol and other psychoactive substances.